THU0291 Incidence of serious gastrointestinal events and inflammatory bowel disease among tildrakizumab-treated patients with moderate to severe plaque psoriasis: data from 3 large randomised clinical trials. (12th June 2018) - Gooderham, M.; Elewski, B.E.; Pariser, D.M.; Sofen, H.; Mendelsohn, A.M.; Cichanowitz, N.; Li, Q.; La Rosa, C.
Abstract : Background: Tildrakizumab, is a high-affinity, humanised, anti–IL-23p19 monoclonal antibody for the treatment of chronic plaque psoriasis. Objectives: Here, we evaluated gastrointestinal (GI) adverse events (AE) and, specifically, cases of inflammatory bowel disease (IBD; ie, Crohn's disease or ulcerative colitis) in the clinical development program for tildrakizumab. Methods: Patients with moderate to severe plaque psoriasis were randomised in 3 large, clinical trials: P05495 (phase 2; NCT01225731 ), reSURFACE 1 (phase 3; NCT01722331 ), and reSURFACE 2 (phase 3; NCT01729754 ). 1 2 In this analysis, we identified serious GI AEs and new-onset or exacerbation of pre-existing IBD from a pooled dataset of tildrakizumab-treated patients from these 3 studies. Doses of tildrakizumab included 5 mg, 25 mg, 100 mg, and 200 mg in P05495 and 100 mg and 200 mg in the reSURFACE studies. Results: In this analysis, we pooled 1911 patients from the 3 trials who received either tildrakizumab 100 or 200 mg. There were no new cases of IBD reported; among 6 patients with a history of IBD randomised to tildrakizumab, none experienced an exacerbation. The numbers (rate per 100 patient-years) of patients with serious GI AEs in the pooled dataset were 8 (0.80) for tildrakizumab 100 mg and 4 (0.43) for tildrakizumab 200 mg. These serious GI AEs included abdominal pain, constipation, diverticulum, dyspepsia, gastritis, thrombosed haemorrhoids, esophageal polyp, pancreatitis (1 patient each) among tildrakizumab 100 mg patients and abdominal hernia, upper abdominal pain, acute pancreatitis, and salivary gland enlargement (1 patient each) among tildrakizumab 200 mg patients. Conclusions: In this post-hoc analysis of patients from 3 large randomised clinical trials, serious GI AEs were infrequent and there were no new cases of IBD or exacerbations of IBD. References: [1] Papp, et al. Br J Dermatol2016;174(6):1426. [2] Reich, et al. Lancet2017;390(10091):276–288. Acknowledgements: This study was funded by Merck and Co., Inc. Editorial support for abstract submission was provided by Fishawack Communications and funded by Sun Pharmaceutical Industries, Inc. Analyses were previously presented at the American Academy of Dermatology. Annual Meeting, San Diego, California, USA, 2018 Disclosure of Interest: M. Gooderham Grant/research support from: Abbvie Inc., Akros Pharma Inc., AMGEN Inc., Boehringer Ingelheim International GmbH, Bristol-Myers Squibb Company, Celgene, Dermira Inc. Eli Lilly and Company, Galderma SA GlaxoSmithKleine Janssen Inc. LEO Pharma MedImmune Merck and Co. Novartis, Pfizer Inc., Regeneron Pharmaceuticals Inc. Roche Laboratories Sanofi Genzyme UCB Valeant Pharmaceuticals Inc., Consultant for: Akros Pharma Inc., AMGEN Inc., Boehringer Ingelheim International GmbH, Celgene, Eli Lilly and Company, Janssen Inc. Novartis, Sanofi Genzyme, Valeant Pharmaceuticals Inc., Speakers bureau: Abbvie Inc. Actelion Pharmaceuticals, AMGEN Inc., Boehringer Ingelheim International GmbH, Celgene, Eli Lilly and Company, Galderma SA, Janssen Inc., LEO Pharma, Novartis, Pfizer Inc., Regeneron Pharmaceuticals Inc., Sanofi Genzyme Valeant Pharmaceuticals Inc., B. Elewski Grant/research support from: Abbvie, Boehringer Ingelheim, Celgene, Incyte, Lilly, Merck, Novartis, Pfizer, Regeneron, Sun Pharma, Viamet, Valeant Pharmaceuticals, Consultant for: Celgene, Lilly, Novartis, Pfizer, Sun Pharma, Valeant; all funds derived from her participation have been paid to her university, D. Pariser Grant/research support from: Abbott Laboratories, Amgen, Asana Biosciences, Bickel Biotechnology, Celgene, Dermavant Sciences, Eli Lilly, LEO Pharma US, Merck and Co., Inc., Novartis, Novo Nordisk, Ortho Dermatologics, Peplin Inc., Pfizer Inc., Photocure ASA, Promius Pharmaceuticals, Regeneron, Stiefel a GSK company, and Valeant Pharmaceuticals, Consultant for: Bickel Biotechnology, Biofrontera AG, Celgene Corporation, Dermira, DUSA Pharmaceuticals, LEO Pharma US, Novartis, Promius Pharmaceuticals, Regeneron, Sanofi, TheraVida, and Valeant Pharmaceuticals, H. Sofen Grant/research support from: Amgen, Boehringer Ingelheim, Janssen, Lilly, Merck and Co., Inc. Novartis, Pfizer, Consultant for: Janssen, Lilly, Novartis, Speakers bureau: Janssen, Lilly, Novartis, A. Mendelsohn Employee of: Sun Pharmaceutical Industries, Inc., N. Cichanowitz Shareholder of: Merck and Co., Inc., Employee of: Merck Sharp and Dohme Corp., a subsidiary of Merck and Co., Inc., Kenilworth, NJ, USA, Q. Li Employee of: Merck Sharp and Dohme Corp., a subsidiary of Merck and Co., Inc., Kenilworth, NJ, USA, C. La Rosa Employee of: Merck Sharp and Dohme Corp., a subsidiary of Merck and Co., Inc., Kenilworth, NJ, USA